Pengaruh Kepemimpinan dan Mutasi Jabatan terhadap Kepuasan Kerja Serta Dampaknya pada Kinerja Pegawai (Studi Pada Dinas Pendidikan Dayah Kabupaten Bireuen) - Khadijatul Musanna; Fauzi Fauzi; M. Ferdiananda Chadafi (Singkite Journal, 2025)
Employee satisfaction and performance analysis is a necessity. This study examines the effects of leadership and job transfers quantitatively through inferential statistics using path analysis. The study involved 39 employees at the Bireuen Regency Dayah Education Office. The results showed: (1) there was a direct and indirect effect of leadership on job satisfaction, through job transfers, of 29.82%, and a 39.04% effect on performance. (2) there was a direct and indirect effect of job transfers on job satisfaction, through leadership, of 29%, and a 37.31% effect on performance. (3) Leadership and job transfers simultaneously had an effect on employee job satisfaction of 77.78% and a 20.27% effect on employee performance.